CYP2C19 gene polymorphism in Ningxia - Yang, Zhen; Xie, Yunqian; Zhang, Daya; Zou, Yan; Li, Ximei; Chen, Runxiang; Zhang, Xiaodong; Chen, Shiju; Bai, Feihu (Pharmacological reports, 2023)
Background Poor metabolizer (PM) status of CYP2C19 can be a predisposing factor for developing gastric cancer in H. pylori -infected patients. It is unclear whether PM status of CYP2C19 can also be a potential factor for H.pylori infection in healthy people. Methods We used high-throughput sequencing to detect single nucleotide polymorphisms (SNPs) at just three loci, rs4244285 (CYP2C19*2), rs4986893 (CYP2C19*3) and rs12248560 (CYP2C19*17), to identify the exact CYP2C19 alleles corresponding to the mutated sites. We determined CYP2C19 genotypes of 1050 subjects from 5 cities of Ningxia from September 2019 to September 2020 and evaluated the potential correlation between H.pylori and CYP2C19 gene polymorphisms. Clinical data were analyzed using χ2 tests. Results The frequency of CYP2C19*17 in Hui (3.7%) was higher as compared to Han (1.4%) in Ningxia ( p = 0.001). The frequency of CYP2C19*1/*17 of Hui (4.7%) was higher as compared to Han (1.6%) in Ningxia ( p = 0.004). The frequency of CYP2C19*3/*17 of Hui (1%) was higher as compared to Han (0%) in Ningxia ( p = 0.023). The frequencies of alleles ( p = 0.142) and genotypes ( p = 0.928) were not found to be significantly different among the different BMI groups. The frequencies of four alleles between H. pylori positive and negative groups were not found to be statistically different ( p = 0.794). The frequencies of the different genotypes between H. pylori positive and negative groups were not statistically different ( p = 0.974), and no statistical difference was observed between the different metabolic phenotypes ( p = 0.494). Conclusion There were regional differences observed in CYP2C19*17 distribution in Ningxia. The frequency of CYP2C19*17 in Hui was higher than in Han of Ningxia. No significant relationship was found between CYP2C19 gene polymorphism and susceptibility to H. pylori infection.